The house on Hope Street - Steel, Danielle (London : Corgi Books, 2001)
Life was good for Liz and Jack Sutherland, but it all fell apart when an errand ended in tragedy. Powered by her children's love, Liz finds the strength to carry on, until an accident sends her oldest son to the hospital and brings a doctor named Bill Webster into her life
Keywords: Mothers and sons -- Fiction; Physicians -- Fiction; Widows -- Fiction; California, Northern -- Fiction